Skin microbiota and diabetic foot ulcers - Jiaqi Lou; Ziyi Xiang; Xiaoyu Zhu; Jiliang Li; Guoying Jin; Shengyong Cui; Neng Huang; Xin Le; Youfen Fan; Qionghui Sun (Frontiers in Microbiology)
Skin microbiota is the microbial population on the skin surface, which has a symbiotic relationship with the host skin and plays an important role in maintaining skin health and regulating immune responses. In patients with diabetic foot ulcers (DFUs), the skin microbiota is unbalanced. The abundance of pathogenic bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa increases, forming biofilms, destroying the skin barrier function, aggravating infection, and leading to poor wound healing. Studies have shown that the diversity of skin microbiota is positively correlated with the severity of ulcers, and regulating its composition and function may be an important strategy to improve DFUs healing. In recent years, with the development of molecular biology technology, progress has been made in the study of skin microbiota, such as 16S rRNA gene sequencing technology to understand its composition changes and explore the interaction mechanism with the host immune system. Based on this, some new therapeutic approaches are being explored, such as the use of probiotics or antibacterial drugs to modulate the composition of the microbiota and the development of microbiota-based personalized treatment regimens. However, there are still challenges in current research. For example, the composition and function of skin microbiota are affected by many factors, and there are relatively few studies on other microorganisms such as fungi and viruses. In the future, it is necessary to further explore its diversity and the interaction mechanism with the host, and develop more effective treatment methods to improve the prognosis of patients with DFUs.